HLA-B alleles and complotypes in Mexican patients with seronegative spondyloarthropathies. Issue 11 (November 1994) - Vargas-Alarcón, G; Garcia, A; Bahena, S; Melin-Aldana, H; Andrade, F; Ibañez-de-Kasep, G; Alcocer-Varela, J; Alarcón-Segovia, D; Granados, J
Abstract : OBJECTIVES–To analyse major histocompatibility complex (MHC) haplotypes in Mexican mestizo patients with seronegative spondyloarthropathies (SSpA) and normal controls, to discover if there are other antigens, besides B27, in the HLA region that might show association with the disease. METHODS–The study included 100 Mexican mestizo patients with SSpA and 200 of their first degree relatives. These groups were compared with 85 ethnically matched controls. The class I and class III MHC antigens were obtained by standard methods. The significance of differences between patients and controls was tested by chi 2 analysis; linkage disequilibrium among the different alleles in each haplotype was estimated by computing delta values. RESULTS–We found a significantly increased frequency of the HLA-B27 antigen (pcorr. = 1 x 10(-5), odds ratio (OR) = 33.4, 95% confidence interval (CI) = 9.3-142.0). In the group of 45 SSpA patients negative for the B27 antigen, independent increased frequencies of HLA-B49 antigen (pcorr. = 0.03, OR = 6.5, 95% CI = 1.5-32.8)) and the FC31 complotype (pcorr. = 0.04, OR = 3.7, 95% CI = 1.2-11.1) were found. Significant delta values were obtained for the [B27;SC30] haplotype (p = 0.0005) but not for haplotypes marked by the FC31 complotype. HLA-B antigens on the homologous chromosome in B27 positive patients were mainly HLA-B51 (18%) and HLA-B60 (16%); however, the observed genotypes B27/B51 and B27/B60 were not significantly different than expected from the allele frequencies alone. CONCLUSIONS–These data suggest that in Mexicans additional genes within the MHC region besides the HLA-B27 antigen, might be related to the genetic susceptibility for developing SSpA. Relevant antigens included the HLA-B49 and the FC31 complotype.